South Africa's National Development Plan - democratic developmental state model in action? - Chilenga, Thokozani Jean (My University, 2015)
The National Development Plan (NDP) was introduced before Parliament in 2012. The NDP describes itself as a plan for a democratic developmental state. Therefore this research will discuss the concepts of a developmental state and its corollary, the democratic developmental state, whilst trying to ascertain whether the NDP is a prudent and achievable plan for such a state. The main research problems that arise are around the formulation of the plan. The research finds that although the NDP is a prudent plan, there will be issues with its achievability if the issues raised are not dealt with. This is because development is primarily a political process which requires political forces to drive development.
Thesis (M.A.) University of the Witwatersrand, Faculty of Human Sciences (Political Studies), 2015